Imagining Queer Chican@s in the Post-Borderlands - T. Jackie Cuevas (Revue LISA)
This paper reveals how the tension of choosing between ethnic solidarity and non-normative gender/sexual identity continues to trouble Chican@/Latin@ writers, as evidenced in Felicia Luna Lemus’ novel Like Son (2007). Lemus's fiction serves as a prime example of how queer and genderqueer literary figures struggle — and often fail —to imagine themselves as desirable subjects of an emerging Latinotopia. Even as Latina/o presence further permeates the U.S. popular imaginary, queer Latin@ texts such as Lemus's remain attentive to the ongoing marginalization of non-normative genders and sexualities within Latinidad.